1993
DOI: 10.1111/j.1360-0443.1993.tb02149.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significant‐other Behavior Questionnaire (SBQ): an instrument for measuring the behavior of significant others towards a person's drinking and abstinence

Abstract: The psychometric properties of the Significant-other Behavior Questionnaire (SBQ), an instrument measuring the specific social support in terms of the patient's drinking. Assessments of the significant other's behavior in the presence of the patient drinking is provided by both the patient and significant other. Data from the two SBQ forms were analyzed with a principal axis factor analytic procedure with varimax rotation. The scales were similar for the two forms with four behavioral reactions, withdraw from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Most empirical work to date has focused on how adult partners cope with a loved one's alcohol problem (Gorman & Rooney, 1979;Holmila, 1994;Love, Longabaugh, Clifford, Beattie, & Peaslee, 1993;Orford et al, 1975;Schaffer & Tyler, 1979;Wiseman, 1980), although some authors have reported on partner-focused interventions that targeted coping skills and influence tactics in response to the drinking (Barber & Crisp, 1995;Dittrich, 1993;Dittrich & Trapold, 1984;Meyers, Miller, Smith, & Tonigan, 2002;Rychtarik, Carstensen, Alford, Schlundt, & Scott, 1988;Sisson & Azrin, 1993;Thomas, Yoshioka, & Ager, 1994;Thomas, Yoshioka, and Ager, 1996;Yoshioka, Thomas, & Ager, 1992). Of particular relevance to partner enabling, Dittrich and Trapold (1984) administered a brief treatment package to 52 women living with an alcohol-dependent person.…”
Section: Introductionmentioning
confidence: 99%
“…Most empirical work to date has focused on how adult partners cope with a loved one's alcohol problem (Gorman & Rooney, 1979;Holmila, 1994;Love, Longabaugh, Clifford, Beattie, & Peaslee, 1993;Orford et al, 1975;Schaffer & Tyler, 1979;Wiseman, 1980), although some authors have reported on partner-focused interventions that targeted coping skills and influence tactics in response to the drinking (Barber & Crisp, 1995;Dittrich, 1993;Dittrich & Trapold, 1984;Meyers, Miller, Smith, & Tonigan, 2002;Rychtarik, Carstensen, Alford, Schlundt, & Scott, 1988;Sisson & Azrin, 1993;Thomas, Yoshioka, & Ager, 1994;Thomas, Yoshioka, and Ager, 1996;Yoshioka, Thomas, & Ager, 1992). Of particular relevance to partner enabling, Dittrich and Trapold (1984) administered a brief treatment package to 52 women living with an alcohol-dependent person.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred sixty-three alcoholics and 157 of their significant others (not all were spouses or partners) completed an SBQ, indicating the frequency of the coping behaviors exhibited by the significant others during the previous 6 months. Data from the two samples revealed that the SBQ possessed strong internal consistencies, and comparison of patient and significant other perceptions of the same behavioral responses were highly related (r = .73) and showed convergent and divergent validity for three of the four subscales (Love et al, 1993). However, weak or absent relationships were found between the SBQ and an index measure of alcohol involvement before treatment.…”
Section: Recent Studiesmentioning
confidence: 92%
“…Analysis of an alcohol-specific 62-item instrument, the Significant-Other Behavior Questionnaire (SBQ), was the subject of a study examining social support behaviors among alcoholics who sought treatment (Love, Longabaugh, Clifford, Beattie, & Peaslee, 1993). These behaviors were classified into two types: those exhibited by the significant others when the alcoholic was drinking, and those exhibited when the alcoholic was not drinking.…”
Section: Recent Studiesmentioning
confidence: 99%
“…These issues were also mentioned by Azrin [16] and by all those who have worked to introduce Concerned Significant Others into the treatment of alcoholic patients [21,22].…”
Section: Discussionmentioning
confidence: 99%